Desafios ao educador na transição do quinto para o sexto ano nas escolas públicas do Estado de São Paulo: uma proposta de formação - Borges, Renata Sales de Moraes (2015)
This study discusses the transition of students from the fifth to the sixth grade of elementary school, considering the expectations in relation to this reality, to demonstrate to teachers who work with these groups the need to adopt a professional stance based on a differentiated formation, since this transition can still be characterized by its ruptures and discontinuities in the pedagogical work. In this sense, the research aims to: build a proposal for continuing education, to be developed along the teachers of elementary school II, reflecting on the passage of pupils from the fifth to the sixth grade. And specific objectives: Enumerating the difficulties teachers experience in relationship with the students of the sixth grade; Identify the characteristics of the students, which are desirable for teachers from early years of elementary school II; Reflect on the processes of change necessary for the reconstruction of teacher-student relationships. The investigation was developed in the form of bibliographic and documentary research, and supported in consultation with professors in the sixth year of a school in the State schools, by the application of a questionnaire, to the construction of the proposed continuing education. The research has revealed, throughout the process, that there are several factors that, directly or indirectly, influence the transition from the fifth to the sixth grade, both for students and for teachers who receive them. One aspect, however, stood out among the others: the student is alone in this passage, because it is not understood as a new space in the process of schooling. The children, most of the time, feel and suffer in silence, or defend themselves inappropriately because it is a transition invisible and unknown by their teachers